Conflict Resolution in Selected Christ Apostolic Church Congregations in Yorubaland, 1990-2000 - Ajayi, David Olusegun (2015)
The study examined conflict resolution in selected Christ Apostolic Church (CAC) congregations in Yorubaland between 1990 and 2000 A.D. It also identified the impact of the conflicts on the CAC congregations. In addition, the study examined the impact of the conflict on the general populace. This was with a view to unravelling the causes of schism in the CAC.